(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A reliable power supply is one that can maintain voltage within a predetermined safety margin. Power systems need to be able to handle voltage well in order to keep up with the increasing demand for electricity and maintain safety. In this study, STATCOM’s adaptive PI control is implemented to regulate power system voltage. The gains of the controller can be adjusted rapidly using this knob. Using this approach, the correct system response can be accomplished in the presence of delays. The effectiveness of the developed controller is evaluated for non-linear loads.